CRIANÇA, COMUNICAÇÃO E CONSUMO: UM ESTUDO DOS CANAIS DE BRINQUEDO NO YOUTUBE - PEREIRA, EVERALDO (2020)
This research have as theme child, communication and consumption and, as object, toy channels on YouTube. The general objective is to study the child as a subject in the process of symbolic construction within the relationship between communication and consumption from a comprehensive perspective, sometimes opposite and sometimes complementary to visions that focus attention on the child as a vulnerable part, and even sometimes as a simple object or victim in this relationship. The research question concerns how pre-literate children relate to the imaginary content of toy video streaming channels, not as isolated individuals but as social subjects who are, making this relationship a process complex, subject to different mediations and also to a diversity of interpretations. The theoretical point of view, we use the assumptions of communication for consumption, the knowledge society, the ethnography of communication and the cultural mediations of communication. Likewise a methodological point of view, we are guided by the ideas of multiperspectivism (Douglas Kellner), depth hermeneutics (John B. Thompson) and understanding, in line with the research group “Da Compreensão como Método” (Understanding as a method). The results contribute to the formation of a conviction about how the process of child construction occurs as a subject of communication. This work, also, intends to help in understanding how the speed of media technologies alter children's behaviors, fragments their sociability, generates new demands of children, re-signifies family and affective bonds, changes consumer relations and changes the meaning of children, toys and play.